Abdominal ultrasound : step by step - Block, Berthold (Thieme, 2016)
That straight-forward approach, coupled with more than 1,000 high-quality images and illustrations, enables hand-on learning, yielding the ability to assimilate these techniques quickly and adeptly. This is a stellar resource that provides the requisite tools ... -- Doody's Review (starred review) This third edition of a well-established text from Berthold Block maintains the same style and clarity as previous editions, taking the novice ultrasound practitioner through a series of steps across systems and levels towards scanning competency and evaluation of the findings. -- RAD Magazine The thi.